Single-phase focused ultrasound surgery for 15-leiomyoma and huge leiomyoma patients - Minh Duc Nguyen (Wolters Kluwer Medknow Publications, 2018)
Focused ultrasound surgery is a potential noninvasive surgery for eliminating leiomyoma. In this clinical image, we introduced an alternative role of this method for cases of multiple leiomyomas and huge leiomyoma with effective outcomes.